Prenatal development of the uterus in the goat - Harshan, K R; Singh, Yashwant; Sharma, D N (The Indian Journal of Animal Sciences, 2012)
An investigation on the normal prenatal development of the uterus in the goat was taken up using 72 normal goat embryos. The uterus developed from the Mullerian ducts which showed their presence as early as 17 days stage. The ducts of both sides united to form the body of the uterus in 51 days embryos. In 52 days embryos a slight increase in the diameter of the duct was noticed in the middle part. Mucosal folds showed their presence at 74 day's. Myometrium started developmg in 80 days embryos. Cervix showed secondary and tertiaty folds at 88 days and 90 days respectively. All the 3 tunics of the uterus and cervix were clearly differentiated in 96 days embryos.